Evaluation of the antifungal efficiency of bioproducts obtained from wild oregano (lippia alba) on fusarium equiseti, the cause of yam rot. (@limentech, Ciencia y Tecnología Alimentaria, 2019)
Most plants produce compounds with antimicrobial properties that can be used in the control of phytopathogenic diseases affecting crops of economic interest, including yams. Given the incessant search for more reliable and beneficial alternatives for the control of pests and diseases in crops, a wide range of research on the use of plant extracts and essential oils that have antifungal effects has opened up. In this study, the antifungal effect of five bioproducts obtained from Lippia alba on fusarium equiseti was determined through the percentage inhibition of mycelial growth and conidia germination. For this purpose, the essential oil was extracted by microwave-assisted hydrodistillation and the extract with its fractions were obtained using ethanol (99%) and column chromatography, in addition, the essential oil was characterized by GC-MS method. The research revealed as main results that the essential oil contains mostly geraniol (51.3%) and citral (35.75%). The best inhibition percentages were achieved using essential oil at a concentration of 200 ppm, achieving 100% inhibition of conidia CFU and at a concentration of 20,000 ppm, 57.4% inhibition of mycelial growth was achieved, indicating that the use of these bioproducts are a good alternative to replace chemical compounds that are used for the control of phytopathogenic diseases.
Keywords: Yam; Lippia alba; fusarium equiset; essential oils; extracts